DIGITAL MARKETING IN THE AGE OF ARTIFICIAL INTELLIGENCE: THE PRESENT AND FUTURE OF ARTIFICIAL INTELLIGENCE TOOLS AND THEIR IMPACT ON BUSINESS MARKETING STRATEGIES (Development Service Industry Management, 2024)
The emergence of artificial intelligence (AI) has profoundly changed digital marketing, creating conditions for the emergence of innovative strategies and tools that improve personalization of interaction with the respondent, efficiency and consumer engagement, etc. Based on this, this article explores new tools and trends in digital marketing related to the emergence, spread and development of artificial intelligence, especially those based on personalization with the help of artificial intelligence, predictive analytics, chatbots, search optimization .By exploring these trends, the article aims to provide an understanding of how businesses can use AI to remain competitive and meet current consumer expectations that exist in a dynamic, technologically changing context.The article discusses the main tools of digital marketing, which are based on the capabilities of artificial intelligence, outlines their overview and description of functionality, gives examples of their use in digital marketing channels of global brands. The article contains an assessment of the advantages and limitations of using such tools to achieve the marketing goals of businesses, potential areas of integration of artificial intelligence capabilities into marketing strategies and channels of interaction with consumers. The forecast of the development of artificial intelligence tools and the trends of expanding their further use in digital marketing and the potential opportunities and challenges associated with the technological implementation of artificial intelligence in the communication, marketing and business processes of enterprises are given.
Keywords: marketing; strategy; business; artificial intelligence